Investigating the Relationship between Primary School Teachers’ Knowledge of Differentiated Instruction and the Frequency of its Implementation to Students with Learning Difficulties - Papanthymou, Anastasia; Darra, Maria (International Research in Education, 2023)
The main purpose of this study is to investigate the perceptions of primary school teachers in the Dodecanese (Greece) regarding the relationship between their knowledge of differentiated instruction and the frequency of its implementation to students with learning difficulties. The research was conducted through quantitative approach using an anonymous electronic questionnaire on a sample of 174 primary school teachers of all specialties in the Dodecanese, during the period from February 13, 2021 to April 28, 2021. The correlation analysis (Spearman's rho) revealed that there is a positive correlation between teachers’ knowledge of differentiated instruction and the frequency of its implementation to students with learning difficulties. Therefore, it was found that as the teachers' knowledge of differentiated instruction practices increases, the frequency of their implementation increases.